2022
DOI: 10.2147/ijn.s370235
|View full text |Cite
|
Sign up to set email alerts
|

Cubosomes for Enhancing Intestinal Absorption of Fexofenadine Hydrochloride: In situ and in vivo Investigation

Abstract: Purpose The aim of this work was to probe cubosomes for enhanced intestinal absorption and oral bioavailability of poorly absorbable fexofenadine HCl (FEX-HCl). Materials and Methods Two cubosomal systems were fabricated utilizing glyceryl mono-oleate, a lyotropic mono lamellar lipid as oil phase and poloxamer407 as stabilizer at weight ratios of 8:2 and 7:3. The morphology of cubosomes was researched using transmission electron microscopy (TEM) and particle size was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…All the prepared solutions were kept at 37 ± 0.5 ◦ C prior to intestinal in situ perfusion to simulate the body physiological temperature, with the solution pH values being adjusted to that of the perfused intestinal segment. The pH values of the prepared solutions were 6.6 for duodenum perfusion, 7.4 for jejuno‐ileum, and 6.8 for colon segment perfusion (Sultan et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…All the prepared solutions were kept at 37 ± 0.5 ◦ C prior to intestinal in situ perfusion to simulate the body physiological temperature, with the solution pH values being adjusted to that of the perfused intestinal segment. The pH values of the prepared solutions were 6.6 for duodenum perfusion, 7.4 for jejuno‐ileum, and 6.8 for colon segment perfusion (Sultan et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, drug absorption is generally facilitated through the transcellular pathway. 105 An in vivo study investigating the anti-inflammatory effects of fexofenadine hydrochloride in rabbits substantiated the superiority of a cubosomal carrier over an aqueous drug dispersion. 105 Huang et al reported the successful implementation of a cubosome-based drug delivery system for glaucoma treatment using timolol maleate (TM).…”
Section: Cubosomesmentioning
confidence: 96%
“…105 An in vivo study investigating the anti-inflammatory effects of fexofenadine hydrochloride in rabbits substantiated the superiority of a cubosomal carrier over an aqueous drug dispersion. 105 Huang et al reported the successful implementation of a cubosome-based drug delivery system for glaucoma treatment using timolol maleate (TM). Ex vivo corneal permeability experiments revealed an elevated penetration of TM cubosomes compared to commercially available eye drops, indicating an enhancement in corneal permeability, increased retention time, and improved bioavailability of ocular drugs for ocular disease treatment.…”
Section: Cubosomesmentioning
confidence: 96%
“…Usually, drugs transported to lymph should be highly lipophilic and should be associated with chylomicron. M cell pathway and other mechanisms of lymphatic transport can co-occur in the cases that hydrophilic drug-loaded LLCs cannot be taken up into epithelial cells as intact particles [ 17 , 19 , 75 ]. Multiple mechanisms of lymphatic transport including M cells, chylomicrons, and transcellular and paracellular pathways at the tight junction of epithelial cells have been reported [ 65 , 67 , 76 ].…”
Section: Facilitating Oral Drug and Vaccine Delivery Using Llc System...mentioning
confidence: 99%